2018
DOI: 10.3390/ijms19103040
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Signaling Pathway in Endothelial Progenitor Cell Biology for Vascular Medicine

Abstract: The Hedgehog (HH) signaling pathway plays an important role in embryonic and postnatal vascular development and in maintaining the homeostasis of organs. Under physiological conditions, Sonic Hedgehog (SHH), a secreted protein belonging to the HH family, regulates endothelial cell growth, promotes cell migration and stimulates the formation of new blood vessels. The present review highlights recent advances made in the field of SHH signaling in endothelial progenitor cells (EPCs). The canonical and non-canonic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 83 publications
(127 reference statements)
1
13
0
Order By: Relevance
“…The proangiogenic potential of the Hh signaling agonists is of growing interest in the treatment of ischemic diseases especially myocardial infarction and peripheral artery diseases as pointed out in several reviews [17,18,19,20,21,22]. However, it is a prerequisite to fully understand mechanisms driving the exogenous Hh part in the setting of ischemia-induced tissue injury, (1) because the role of the endogenous Hh signaling is still unclear and discordant and (2) because of the potential carcinogenic effect of Shh.…”
Section: Blood Vessel Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…The proangiogenic potential of the Hh signaling agonists is of growing interest in the treatment of ischemic diseases especially myocardial infarction and peripheral artery diseases as pointed out in several reviews [17,18,19,20,21,22]. However, it is a prerequisite to fully understand mechanisms driving the exogenous Hh part in the setting of ischemia-induced tissue injury, (1) because the role of the endogenous Hh signaling is still unclear and discordant and (2) because of the potential carcinogenic effect of Shh.…”
Section: Blood Vessel Maturationmentioning
confidence: 99%
“…Moreover, Hh ligands have been shown to regulate blood vessel maturation [14], integrity [15], and arterial differentiation [16]. As a consequence, the therapeutic potential of Hh signaling agonists for vascular diseases is of growing interest [17,18,19,20,21,22]. However, molecular and cellular mechanisms underlying the role of the Hh signaling in vascular biology remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Other key miRNAs involved in the regulation of endothelial functions include miRNA-155 which targets eNOS and regulating the vascular tone [92], and miRNA-125b targeting VE-cadherin-5 and therefore inhibiting the formation of vessel tubes [93]. Many other miRNAs were identified as contributors to endothelial cells physiopathology, as covered by recent reviews [94,95] and reviewed in Table 2.…”
Section: Mirnas In Regulating Necs/tecs Metabolismmentioning
confidence: 99%
“…Hh signaling pathway is an evolutionarily conserved pathway of signal transmission from the cell membrane to the nucleus to involve in normal embryonic development [7], the maintenance of airway epithelial progenitors and pluripotent cells [8], regeneration of the lung and prostate epithelium for tissue repair [9], and various stages of carcinogenesis in different tumors [10]. Sonic Hedgehog (SHH), a secreted protein belonging to the HH family, have been reported to involve in endothelial cell growth, cell migration and the formation of new blood vessels [11]. Deregulation of the SHH signaling pathway has been implicated in lymphoma such as small lymphocytic lymphoma, plasma cell myeloma, mantle cell lymphoma, diffuse large B-cell lymphoma, chronic myelogenous leukemia, acute leukemias and anaplastic lymphoma kinase (ALK) -positive anaplastic large cell lymphoma, as well as sporadic cancers such as gastric cancer, basal cell carcinoma, medulloblastoma, pancreatic cancer, breast cancer, ovarian cancer, small-cell lung cancer, and colorectal cancer [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Sonic Hedgehog (SHH), a secreted protein belonging to the HH family, have been reported to involve in endothelial cell growth, cell migration and the formation of new blood vessels [11]. Deregulation of the SHH signaling pathway has been implicated in lymphoma such as small lymphocytic lymphoma, plasma cell myeloma, mantle cell lymphoma, diffuse large B-cell lymphoma, chronic myelogenous leukemia, acute leukemias and anaplastic lymphoma kinase (ALK) -positive anaplastic large cell lymphoma, as well as sporadic cancers such as gastric cancer, basal cell carcinoma, medulloblastoma, pancreatic cancer, breast cancer, ovarian cancer, small-cell lung cancer, and colorectal cancer [10][11][12][13][14]. Singh et al found that inhibition of ALK tyrosine kinase down-regulates SHH signaling pathway in ALK-positive anaplastic large cell lymphoma [14].…”
Section: Introductionmentioning
confidence: 99%